PENDAMPINGAN MAJLIS TAKLIM ALHAMDULILLAH YANG TERKENA DAMPAK COVID-19 MELALUI BUDIDAYA ULAT HONGKONG DI PEKANBARU - Yendraliza, Yendraliza; Oksana, Oksana; Ariyanti, Ervina (Universitas Padjadjaran, 2025)
The nutritional content of mealworm caterpillars has been studied and its benefits have been widely reported. Mealworm caterpillars are utilized as feed for poultry and fish, and even as ingredients in cosmetic products. Mealworm caterpillar farming does not require a large area. The feed used can be supplemented with household or market waste. Mealworm caterpillar farming containers can also be made from wood scraps or thick cardboard scraps. This community service aims to strengthen family resilience by increasing household income through mealworm caterpillars farming. The method used in this program is the Asset-Based Community Development (ABCD) method. This program involved 5 members of the Majlis Taklim, with a total distribution of 1 kg of mealworm breeding stock with 30 rearing boxes. This community service program was conducted from June to October 2023. The program implementation of the service begins with the preparation for caterpillar cultivation, caterpillar enlargement, harvesting, and marketing. The program results can help family resilience by increasing the knowledge of Majlis Taklim about the cultivation of mealworm caterpillar breeding. The Participating farmers were able to increase their household income, with an initial investment of IDR 80,000 yielding IDR 180,000 within 10 days. The findings suggest that mealworm caterpillar farming can serve as an alternative to increase the income of communities affected by Covid-19.Kandungan ulat hongkong sudah diteliti dan manfaatnya sudah banyak dilaporkan. Ulat hongkong dimanfaatkan sebagai pakan unggas dan pakan ikan, bahkan digunakan untuk bahan kosmetik. Beternak ulat hongkong tidak memerlukan tempat yang luas. Pakan yang diberikan dapat bersinergi dengan limbah rumah tangga atau limbah pasar. Kandang ulat hongkong juga dapat dibuat dari sisa-sisa kayu atau sisa kartun yang tebal. Tujuan pengabdian ini adalah membantu ketahanan keluarga dengan meningkatkan pendapatan masyarakat dengan budidaya ulat hongkong. Metode yang digunakan dalam pengabdian ini adalah metode ABCD. Pengabdian ini melibatkan 5 orang majlis taklim, total penyebaran induk ulat hongkong 1 kg dengan 30 kotak kandang yang digunakan. Pengabdian dilakukan bulan Juni sampai dengan bulan Oktober 2023. Pelaksanaan pengabdian diawali dengan persiapan budi daya ulat, pembesaran ulat, pemanenan dan pemasaran ulat hongkong. Hasil pengabdian dapat membantu ketahanan keluarga dengan menambah pengetahuan, ketrampilan dan pemasukan majlis taklim tentang budi daya beternak ulat hongkong. Peternak yang terlibat dapat meningkatkan pendapatan keluarga dengan modal Rp. 80.000,- dapat menghasilkan Rp. 180.000,- dalam waktu 10 hari. Hasil dari pengabdian ini adalah beternak ulat hongkong dapat menjadi alternatif untuk meningkatkan pendapatan Masyarakat yang terkena dampak Covid-19.